Effect of calcium hydroxide on mechanical strength and biological properties of bioactive glass. (August 2016) - Shah, Asma Tufail; Batool, Madeeha; Chaudhry, Aqif Anwar; Iqbal, Farasat; Javaid, Ayesha; Zahid, Saba; Ilyas, Kanwal; bin Qasim, Saad; Khan, Ather Farooq; Khan, Abdul Samad; ur Rehman, Ihtesham
Abstract: In this manuscript for the first time calcium hydroxide (Ca(OH)2 ) has been used for preparation of bioactive glass (BG-2) by co-precipitation method and compared with glass prepared using calcium nitrate tetrahydrate Ca(NO3 )2 ·4H2 O (BG-1), which is a conventional source of calcium. The new source positively affected physical, biological and mechanical properties of BG-2. The glasses were characterized by Fourier transform infrared (FTIR), X-Ray Diffractometer (XRD), Scanning Electron Microscopy (SEM), Thermogravimetric Analysis/Differential Scanning Calorimetry (TGA-DSC), BET surface area analysis and Knoop hardness. The results showed that BG-2 possessed relatively larger surface properties (100 m 2 g −1 surface area) as compared to BG-1 (78 m 2 g −1 ), spherical morphology and crystalline phases (wollastonite and apatite) after sintering at lower than conventional temperature. These properties contribute critical role in both mechanical and biological properties of glasses. The Knoop hardness measurements revealed that BG-2 possessed much better hardness (0.43±0.06 GPa at 680 °C and 2.16±0.46 GPa at 980 °C) than BG-1 (0.24±0.01 at 680 °C and 0.57±0.07GPA at 980 °C) under same conditions. Alamar blue Assay and confocal microscopy revealed that BG-2 exhibited better attachment and proliferation of MG63 cells. Based on the improved biological properties of BG-2 as a consequent of novel calcium source selection, BG-2 is proposed as a bioactive ceramic for hard tissue repair and regeneration applications. Graphical abstract: Highlights: Calcium hydroxide, a better source for calcium oxide in Bioactive glass. Ca(OH)2 is a better network modifier and improves the network connectivity. Calcium source affects the mechanical strength of glass. Effect of calcium source on cell attachment and cell proliferation.